An Investigation into the Prevalence of Enamel Hypoplasia in an Urban Area Based on the Types and Affected Teeth - Valbona Disha; Marin Zaimi; Elizana Petrela; Fatbardha Aliaj (MDPI AG, 2024)
Enamel hypoplasia (EH) is a qualitative defect, and it can have a significant impact on oral health. The aim of this study was to evaluate the prevalence of enamel hypoplasia in urban area in Albania. Methodology: In total, 234 children of both sexes aged 8-12 years old were randomly selected in five schools in Tirana, Albania. They underwent an intra-oral examination. Diagnostic criteria were in accordance with a European meeting on MIH held in Athens, 2003, and the FDI. Medical history was retrieved using questionnaires, and data obtained from clinical examination were recorded. Results: The prevalence of enamel hypoplasia was 12.8%. The most commonly occurring enamel hypoplasia was the mild type (58.62%). The mandibular first molar showed the highest prevalence of enamel hypoplasia (19.5%), and the maxillary canines and premolars were the least affected (2.3%). In this study, medical story did not have a significant effect on enamel hypoplasia. Conclusions: The prevalence of enamel hypoplasia remains high at 12.8%. Interestingly, the features of enamel hypoplasia were consistent across both sexes, with no correlation found between them. The predominant occurrence of mild enamel hypoplasia underscores the importance of implementing oral hygiene strategies in schools to mitigate its progression.